Antipsychotic drugs induce vascular defects in hematopoietic organs. Issue 10 (6th September 2022) - Deng, Zhao‐hua; Zhong, Jing; Jiang, Hai‐lin; Jeong, Hyun‐Woo; Chen, Jian‐wei; Shu, Ya‐hai; Tan, Ming; Adams, Ralf H.; Xie, Ke‐ping; Chen, Qi; Liu, Yang
Abstract: Antipsychotic agents are clinically utilized to treat schizophrenia and other mental disorders. These drugs induce neurological and metabolic side effects, but their influence on blood vessels remains largely unknown. Here, we show that haloperidol, one of the most frequently prescribed antipsychotic agents, induces vascular defects in bone marrow. Acute haloperidol treatment results in vascular dilation that is specific to hematopoietic organs. This vessel dilation is associated with disruption of hematopoiesis and hematopoietic stem/progenitor cells (HSPCs), both of which are reversible after haloperidol withdrawal. Mechanistically, haloperidol treatment blocked the secretion of vascular endothelial growth factor A (VEGF‐A) from HSPCs. Genetic blockade of VEGF‐A secretion from hematopoietic cells or inhibition of VEGFR2 in endothelial cells result in similar vessel dilation in bone marrow during regeneration after irradiation and transplantation. Conversely, VEGF‐A gain of function rescues the bone marrow vascular defects induced by haloperidol treatment and irradiation. Our work reveals an unknown effect of antipsychotic agents on the vasculature and hematopoiesis with potential implications for drug application in clinic.